TINGKAT KEBERHASILAN PERCEPATAN MOLTING KEPITING BAKAU (SCYLLA SERRATA) DENGAN PERLAKUAN SALINITAS BERBEDA DALAM WADAH TERKONTROL SKALA LABORATORIUM DI SEKOLAH ALAM DESA KALIWLINGI BREBES - Aji, Samudra; Suyono; Mulatsih, Sri (Universitas Pancasakti Tegal, 2023)
Mangrove crabs (Scylla Serrata) are important products on a small scale in australia and asia. High economic value is the advantage of mangrove crab (Scylla Serrata) commodity. The needs of local and international markets are increasing. This pattern is a big challenge. The purpose of this study is to analyze the molting crab molting time (Scylla Serrata) with different salinity training and to find the efficiency of controlled containers with different salinity. The type of research used is experimental research. The design used is a completely randomized design (CRD) with three preparations and three replications using a controlled container. The treatment consists of different salinity methods with the 20 ppt, 25 ppt, 30 ppt salinity settings. The crab used is mangrove crab (Scylla Serrata) with hard carapace. The test parameters are the length of time of molting, mangrove crabs, from hard-crested crabs to increased, molting with different salinity methods. Data obtained from the differences in the length of time of mangrove crab molting using a variety of assistance were verified in quantitative descriptive. The results of this study indicate that the 30 ppt salinity training method is the training that produces the best molting, which is 15-25 days compared to other conservation. While controlled containers show the results that mangrove crabs (Scylla Serrata) can live in containers with clean air systems with salinity and rotated water systems, controlled containers provide advantages in terms of funding, price, and environmentally friendly for the maintenance of mangrove crabs.